2000
DOI: 10.1007/bf02236857
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rectal cancer morbidity and mortality in patients with familial adenomatous polyposis after colectomy and ileorectal anastomosis

Abstract: Patients on whom ileorectal anastomosis was performed had, despite the high rectal excision rate, a substantial risk of developing cancer in the retained colorectal segment, with an ensuing high mortality. Our results indicate that patients with dense polyposis should undergo restorative proctocolectomy as primary operation for familial adenomatous polyposis. In younger patients with intermediate or sparse polyposis and good expected follow-up compliance, ileorectal anastomosis still is an alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
15
1
1
Order By: Relevance
“…The indications for proctectomy in 195 patients without a metachronous 1953 1957 1963 1960 1970 1967 1973 1976 1979 1985 1982 1988 1991 1994 1997 2000 2003 2006 Year BÜLOW ET AL: ILEORECTAL ANASTOMOSIS IN FAP rectal cancer were: severe rectal adenomatosis (n=163), functional problems (n=7), and unspecified or unknown (n=25). The ten-year cumulative incidence of proctectomy was 18 percent (95 percent CI, [15][16][17][18][19][20][21] for the prepouch period and 16 percent (95 percent CI, [10][11][12][13][14][15][16][17][18][19][20][21][22] for the pouch period. In men, 119 of 295 (40 percent) had a proctectomy during the prepouch period vs. 21 of 106 (20 percent) during the pouch period, but the cumulative risk of proctectomy did not change (P=0.9).…”
Section: Resultsmentioning
confidence: 99%
“…The indications for proctectomy in 195 patients without a metachronous 1953 1957 1963 1960 1970 1967 1973 1976 1979 1985 1982 1988 1991 1994 1997 2000 2003 2006 Year BÜLOW ET AL: ILEORECTAL ANASTOMOSIS IN FAP rectal cancer were: severe rectal adenomatosis (n=163), functional problems (n=7), and unspecified or unknown (n=25). The ten-year cumulative incidence of proctectomy was 18 percent (95 percent CI, [15][16][17][18][19][20][21] for the prepouch period and 16 percent (95 percent CI, [10][11][12][13][14][15][16][17][18][19][20][21][22] for the pouch period. In men, 119 of 295 (40 percent) had a proctectomy during the prepouch period vs. 21 of 106 (20 percent) during the pouch period, but the cumulative risk of proctectomy did not change (P=0.9).…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Data from the Polyposis Registry in Sweden indicate a 25.7% cumulative risk at 70 years of age. 30 Pathology (presence of villous adenomas, dysplasia, polyps number, size, and shape) and APC gene mutation locus have also been associated with this risk. [30][31][32][33] During an average follow-up of 91 months (three to 57), six out of 36 IRA patients (16.6%) in the present series developed rectal cancer.…”
Section: Discussionmentioning
confidence: 97%
“…30 Pathology (presence of villous adenomas, dysplasia, polyps number, size, and shape) and APC gene mutation locus have also been associated with this risk. [30][31][32][33] During an average follow-up of 91 months (three to 57), six out of 36 IRA patients (16.6%) in the present series developed rectal cancer. Median ages at primary colectomy for FAP and at rectal cancer diagnosis were 45.8 and 50.6 years, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…11 The rate of cancer development in the residual rectum following IRA depends on the surveillance period and the Values in parentheses are percentages IAA total proctocolectomy with ileoanal anastomosis; IPAA total proctocolectomy with ileal-pouch anal anastomosis; APR abdominoperineal resection; EMR endoscopic mucosal resection a One patient required total pelvic exenteration for the pelvic recurrence after IAA age of the patient. 12,13 Studies with follow-up periods of 5 years or longer have reported rates of 7−37%. 6,8,[12][13][14][15][16][17][18][19][20] The risk rate of postoperative rectal cancer in the residual rectum in our study was 30% over a surveillance period of 8.9 years.…”
Section: Discussionmentioning
confidence: 98%